Pengembangan Poklahsar Pempek dan Kemplang Udang di Belo Laut, Kabupaten Bangka Barat Melalui Peningkatan Manajemen Produksi dan Pemasaran - Kurniawan, Ardiansyah Ardiansyah; Kurniawan, Andri Andri; Setyawan, Ryand Daddy; Anjani, Tiara Puspa; Triswiyana, Ira; Permatasari, Ayu (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
Food safety is one of the important elements in improving the quality of processed food products. Digital marketing plays an important role in expanding market share and increasing the number of marketing that can have an impact on improving the welfare of processed food product producers. Community service activities carried out by the academic community of Bangka Belitung University aimed to increase the understanding and awareness of the fisheries processing and marketing group (Poklahsar) of pempek and kemplang of shrimp about food safety and to improve the ability and skills of Poklahsar in branding and digital marketing. Community service is carried out through counseling and training activities in Belo Laut Village, Mentok District, West Bangka Regency, Bangka Belitung Islands Province. The results of community service activities show that Poklahsar was aware and concerned about the urgency of food safety and including the use of food additives in the production of food products. Poklahsar also gave a very good and enthusiastic response to digital marketing training by creating an Instagram account as a digital marketing instrument for Poklahsar pempek and shrimp kemplang. Community service activities really need to be followed up with mentoring activities so that outreach and training activities can continue and contribute to increasing the production and marketing of processed pempek and shrimp kemplang products in Belo Laut Village.